The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cam4.1307
|View full text |Cite
|
Sign up to set email alerts
|

Higher than reported adolescent and young adult clinical trial enrollment during the “Golden Age” of melanoma clinical trials

Abstract: Clinical trial enrollments in adolescents and young adults (AYA) with cancer have historically been lower than those in pediatric and older adult populations. We sought to examine therapeutic trial enrollment rates at our cancer center. We performed a retrospective evaluation of AYA patients treated before and after the first checkpoint inhibitor trial opened at our cancer center in 2007. We examined gender, stage at presentation and insurance status in terms of trial enrollment. We compared the trial particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Three of the 13 AYA studies addressed barriers to patient eligibility . In their study, Shaw and Ritchey found that 6% of patients (8 of 139) aged 15 to 22 years were not enrolled in a study because of ineligibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the 13 AYA studies addressed barriers to patient eligibility . In their study, Shaw and Ritchey found that 6% of patients (8 of 139) aged 15 to 22 years were not enrolled in a study because of ineligibility.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the 13 AYA CCT studies addressed the extent to which a lack of AYA acceptance of a CCT was a barrier to enrollment . CCT enrollment discussions that occurred close to the diagnosis were overwhelming and impaired decision making .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have specifically addressed the topic of melanoma in AYAs, an age group in which melanoma may present with a variety of histological subtypes and differences in biology and clinical history, consequently making any classification arbitrary. In this review, we discuss what is known about the characteristics of melanoma in such young people, comparing them with the ample experience gained on adult melanoma in an effort to shed more light on the issue presented by melanoma in AYAs.…”
Section: Epidemiologymentioning
confidence: 99%
“…The same patient recruitment problems affected the phase II study of ipilimumab on adolescents (i.e., age 12–18 years) with unresectable stage III or IV melanoma; the plan had been to enroll 40 patients, but the study was prematurely closed after only 12 patients had been recruited over a 3.5‐year period . There have nonetheless been reports of a positive trend in the enrollment of young patients in clinical trials in recent years, associated with a statistically insignificant trend towards a better 3‐year OS for AYA patients with advanced disease who were enrolled in clinical trials than for those who were not …”
Section: New Therapeutic Challengesmentioning
confidence: 99%